Asymmetric synthesis of a highly functionalized bicyclo[3.2.2]nonene derivative - Tabuchi, Toshiki; Urabe, Daisuke; Inoue, Masayuki (Beilstein Journal of Organic Chemistry, 2013)
The stereoselective Diels–Alder reaction between an optically active 1,4-dimethylcycloheptadiene and acrolein was effectively promoted by TBSOTf to produce a bicyclo[3.2.2]nonene derivative bearing two quaternary carbons. Seven additional transformations from the obtained bicycle delivered the C2-symmetric bicyclo[3.3.2]decene derivative, a key intermediate in our synthetic study of ryanodine.
Keywords: asymmetric synthesis; C2-symmetry; catalysis; Diels–Alder reaction; Lewis acid; natural product; quaternary carbon